RASIO FINANSIAL DAN FAKTOR LAINNYA: APAKAH BERPENGARUHTERHADAP FIRM VALUE - SAMUEL LUKIYANTO; RUDI SETIADI TJAHJONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Research of Firm Value is to obtain empirical evidence about the probability of profitability, debt to asset ratio, current ratio, firm size, dividend payout ratio, managerial ownership and investment decision on firm value. Research population of this research are consumer cyclical and non-cyclical companies that listed in Indonesia Stock Exchange from 2020 until 2022. There are 36 companies and 108 data selected as a sample by using purposive sampling method. The sample are tested and analyzed using multiple regression method. Result of this research implies that profitability, debt to asset ratio, managerial ownership, and investment decision affect firm value, while current ratio, firm size, and dividend payout ratio not affecting firm value.